Assigning meaning to light verbs in Turkish - Duygu ÖZGE; Gülten ÜNAL; İsa Kerem BAYIRLI (Dilbilim Araştırmaları Dergisi)
Light verb constructions (e.g., give a kiss to somebody) syntactically reflect typical ditransitive structures (e.g., give a violin to somebody) yet it is not clear whether these two structures thematically similar as well. We tested Turkish-speaking adults on their construal of light verb constructions with respect to the number of thematic roles they perceive in the event structure in a rating study. The light verb give with a different noun phrase was used in all critical utterances (e.g., give a response or give an assignment). The noun phrases of these constructions denominalized either by -lA or -lAn+dIr morpheme (e.g., response-lA and assignment-lAn+dIr) were also used as control items. The study concluded that the light verbs with their noun phrase complements contribute to the semantic construal of the event structure and the thematic role assignment processes for the denominalized versions of these structures reflect this meaning construal.